2019
DOI: 10.3390/nu11061323
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Increase in Protein Intake Promotes a Small Additional Improvement in Functional Capacity, But Not in Muscle Strength and Lean Mass Quality, in Postmenopausal Women Following Resistance Exercise: A Randomized Clinical Trial

Abstract: The aim of this study was to evaluate the effect of a moderate increase in protein intake on muscle strength, functional capacity and lean mass quality improvements in postmenopausal women following resistance exercise. Forty-seven postmenopausal women were randomized in two groups: Normal protein (NP, n = 25), who received a dietary plan containing ~0.8 g protein·kg−1·d−1 (recommended dietary allowance—RDA recommendations); and higher protein (HP, n = 22), which a moderate increase in protein intake was recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
(82 reference statements)
0
11
1
Order By: Relevance
“…Sixty‐six out of 74 studies were included in the lean body mass change analysis, utilizing 2665 subjects 33–99 . Six studies presented intervention groups not using RE training 41,46,94,97–99 ; of these, four studies tested protein ingestion exclusively, 41,97–99 and two studies tested protein ingestion in groups without and with resistance exercise 46,94 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixty‐six out of 74 studies were included in the lean body mass change analysis, utilizing 2665 subjects 33–99 . Six studies presented intervention groups not using RE training 41,46,94,97–99 ; of these, four studies tested protein ingestion exclusively, 41,97–99 and two studies tested protein ingestion in groups without and with resistance exercise 46,94 .…”
Section: Resultsmentioning
confidence: 99%
“…Six studies presented intervention groups not using RE training 41,46,94,97–99 ; of these, four studies tested protein ingestion exclusively, 41,97–99 and two studies tested protein ingestion in groups without and with resistance exercise 46,94 . Changes in strength data resulting from the additional protein intervention were extracted from 50 studies testing 2283 subjects for lower‐body strength 33,36–39,43,44,47–49,52–58,61–65,67–70,72,74–78,82,84,86,88–92,94,96,100–104 and only three studies with intervention groups without RE 41,99,105 . Thirty‐four studies tested bench‐press strength 33,36–38,43,47–49,53–55,62–65,67,68,70,72,74,75,77,78,82,84,86–88,90,91,93,95,96,99 with 1049 subjects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1⋅6 g/kg/d) with concomitant RE. In the second trial, the authors reported that higher protein intake improved functional capacity, as measured by the participants' performance on the Short Physical Performance Battery and various walking tests, but did not improve strength or lean mass (108) . Despite being somewhat inconsistent, these findings still show that consuming more protein and completing RE can yield beneficial results.…”
Section: Optimising Protein Nutritionmentioning
confidence: 99%